Catalog of History Manuscrip Collection of Rekso Pustoko Mangkunegaran Library Collection Surakarta: Pembuatan Katalog Manuskrip Sejarah Koleksi Perpustakaan Rekso Pustoko Mangkunegaran Surakarta - Darmarastri, Hayu Adi; Susanto, Susanto; Sutirto, Tundjung Wahdi; Supariadi, Supariadi; Suharyana, Suharyana; Dadtun, Yusana Sasanti; Sudarno, Sudarno (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
ABSTRACT: The Rekso Pustoko Mangkunegaran Library has various types of historical manuscripts, covering history from ancient to modern periods. The existence of these collections is certainly very useful for writing history, especially the history of Java. Unfortunately, there are still many historical researchers in Indonesia who use colonial archival sources such as Besluit, Algemeen Verslag, Memorie van Overgave and documents such as Staatsblad, Rijksblad and Regeering Almanac instead of using existing historical manuscripts. This is due to the difficulties experienced by historical researchers in reading manuscripts which in terms of material are written by hand and use Javanese language and letters. To overcome this problem, it is necessary to catalog the manuscripts. The catalog of historical manuscripts in addition to containing the manuscript code number also contains a synopsis of the contents of the manuscript. This, in addition to making it easier for researchers to find manuscripts, also helps in understanding the contents of historical manuscripts from the Rekso Pustoko Mangkunegaran collection. The purpose of this service is to catalog the historical manuscripts of the Rekso Pustoko Mangkunegaran collection. ABSTRAK: Perpustakaan Rekso Pustoko Mangkunegaran mempunyai berbagai jenis manuskrip sejarah, meliputi sejarah dari periode kuno hingga modern. Keberadaan koleksi-koleksi ini tentu sangat bermanfaat bagi penulisan sejarah terutama sejarah Jawa. Sayangnya, masih banyak peneliti sejarah di Indonesia yang lebih banyak menggunakan sumber arsip kolonial seperti Besluit, Algemeen Verslag, Memorie van Overgave maupun dokumen seperti Staatsblad, Rijksblad dan Regeering Almanak dibandingkan memanfaatkan manuskrip sejarah yang ada. Hal ini dikarenakan kesulitan yang dialami peneliti sejarah dalam membaca manuskrip yang dari segi material ditulis dengan tangan serta menggunakan bahasa dan huruf Jawa. Untuk mengatasi masalah ini diperlukan upaya katalogisasi manuskrip. Katalogisasi manuskrip sejarah selain berisi nomor kode manuskrip juga berisi sinopsis dari isi manuskrip. Hal ini selain mempermudah peneliti dalam menemukan manuskrip juga sekaligus membantu dalam memahami isi manuskrip sejarah koleksi Rekso Pustoko Mangkunegaran. Tujuan dilakukannya pengabdian ini adalah untuk membuat katalog manuskrip sejarah koleksi Rekso Pustoko Mangkunegaran.